2020
DOI: 10.1088/0256-307x/37/1/010301
|View full text |Cite
|
Sign up to set email alerts
|

Critical Scaling Behaviors of Entanglement Spectra*

Abstract: We investigate the evolution of entanglement spectra under a global quantum quench from a short-range correlated state to the quantum critical point. Motivated by the conformal mapping, we find that the dynamical entanglement spectra demonstrates distinct finite-size scaling behaviors from the static case. As a prototypical example, we compute real-time dynamics of the entanglement spectra of a one-dimensional transverse-field Ising chain. Numerical simulation confirms that, the entanglement spectra scales wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In this context, it is interesting to consider whether the ES -as a more precise measure of quantum entanglement than the EE -can be determinated by using the conformal symmetry. In (1 + 1)D critical systems, it is found that the ES can be indeed solved through CFT techniques [24], and the conformal data can be resolved by the ES [25]. Moreover, at the continuum limit, the gap of entanglement spectrum closes and the continuous distribution of the ES is found to be dependent only on the central charge [34].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this context, it is interesting to consider whether the ES -as a more precise measure of quantum entanglement than the EE -can be determinated by using the conformal symmetry. In (1 + 1)D critical systems, it is found that the ES can be indeed solved through CFT techniques [24], and the conformal data can be resolved by the ES [25]. Moreover, at the continuum limit, the gap of entanglement spectrum closes and the continuous distribution of the ES is found to be dependent only on the central charge [34].…”
Section: Introductionmentioning
confidence: 94%
“…In particular, the study of quantum entanglement brings novel insights into understanding critical phenomena in many-body systems. Especially for (1+1)-dimensional [(1+1)D] critical systems in equilibration [11][12][13][14][15][16] and out-of-equilibrium [17][18][19][20][21][22][23][24][25], the intrinsic conformal invariance leads to rigid constrains on physical proprieties, including the structure of quantum entanglement. One of the most important measures of quantum entanglement is the entanglement entropy (EE), defined as the von Neumann entropy of the reduced density matrix of the subsystem ρ A :…”
Section: Introductionmentioning
confidence: 99%
“…The hope is substantiated by the previous results obtained simulating the long-time behavior of quantum systems out-of-equilibrium [13][14][15] and comparing them with the CFT predictions. In previous works [13,[15][16][17], we have identified the low-energy part of the entanglement Hamiltonian as the relevant quantity to focus on in this context. We have shown how the CFT predictions are recovered by focusing on the low-energy part of the entanglement Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the critical behaviors of the entangled spectra is worth studying, as it would provide significant information on the quantum phase transitions. [31]…”
mentioning
confidence: 99%